(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Kerala the beautiful state located in the southern peninsular India is enriched with forty four rivers and plenty of hillocks. Its landscape and greenery makes it a visitors’ paradise. In spite of a well educated, politically and socially motivated population its solid waste efforts are below the benchmark. From past studies it is seen that almost 80 of the municipal solid waste is neither collected nor processed showing the inefficiency of the solid waste management system of the State. The waste generators are classified into four groups for the purpose of this study namely Households, Shop Owners, HotelsRestaurants and Institutions. Similarly stakeholders are classified into Residents’ Associations, Self Help Groups, Non-Government Organisations, Community Based Organisations, Private Companies, Political Parties and Other Agencies. The study attempts to bring to light the role of stakeholders in waste collection services of the municipalities of Kerala. It reveals that institutions get higher benefits from majority of the stakeholder groups.